ANALISIS PEMANFAATAN TUNJANGAN PROFESI GURU BERDASARKAN PERATURAN MENTERI PENDIDIKAN DAN KEBUDAYAAN REPUBLIK INDONESIA NOMOR 19 TAHUN 2019 - Wismandari Harimurti; Uswatun Chasanah; Muhammad Mathori (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2021)
Teacher Professional Allowances are given to teachers who have an educator certificate as an appreciation for their professionalism. The allowance is to raise their dignity dan increase their competence dan finance professional development. This study aims to analyze the use of PNSD Teacher Professional Allowance that occurs in SMAN 1 Patuk Gunungkidul dan analyze how PNSD Teacher Professional Teacher Allowance should be used. The research method used was a qualitative case study. Informants in this study were 25 PNSD teachers who had received the teacher professional allowance. Data collection techniques were carried out by using interviews, documentation dan triangulation, while data analysis techniques used data collection, data reduction, data presentation, descriptive data analysis dan verification dan data validation. The results showed that the use of PNSD teacher profession allowances that occurred did not meet the Permendikbud target number 19 of 2019, where most of the allowances were used to meet family needs including daily needs, education dan travel as well as renovation dan purchase of motorbikes or cars. The use of professional allowances that should be in accordance with Permendikbud No. 19 of 2019, namely most teachers have participated in seminars or workshops, subscribed to newspapers dan Wi-Fi to look for teaching materials, making teaching materials dan buying teaching support tools. They used their allowances to provide social assistance in the community dan schools by giving gifts or rewards to high-achieving students, giving funds to people who have died or are ill dan participating in social funding in schools dan the environment. They also buy books that are relevant in teaching dan teaching activities develop learning material with educational books.